Physical and Chemical Properties of Epoxy Mold Compound As Replacement of Fine Aggregate in Lightweight Concrete As A sustainable Pontoon - BIN MOHAMAD NAZLI, MUHAMMAD ZULHILMI; Hasnida Harun, (Progress in Engineering Application and Technology, 2024)
Due to the growing amount of trash generated worldwide, there is a need for creative and environmentally friendly waste management strategies. This study investigates the utilization of waste epoxy molding compound (EMC) as a strengthening agent in lightweight polyurethane concrete to create environmentally friendly floating pontoons. The objective of the research is to determine the most effective proportion of fine aggregate to waste EMC to create lightweight polyurethane concrete. Additionally, the study will examine the physical and mechanical characteristics of the concrete. The study promotes environmental sustainability by integrating EMC, which reduces landfill waste and improves concrete's buoyancy, strength, and thermal insulation. The experimental findings indicate that the replacement of fine aggregate with waste EMC in polyurethane lightweight polyurethane concrete enhances its compressive strength, density, and buoyancy, rendering it appropriate for use in floating pontoon applications. The materials were characterized using advanced analytical techniques such as Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD). This study provides evidence for the use of sustainable materials and adds to initiatives aimed at reducing waste, in line with the principles of a circular economy.